(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
A thorough computational analysis of the nonlinear, steady-state, laminar convective boundary layer flow of an incompressible Buongiorno nanofluid across an elongating sheet with several slip effects is conducted. This research is important as it models realistic industrial and biomedical applications where slip conditions occur at surfaces, such as in microfluidic devices. Understanding these effects enhances control over heat and mass transmission. The governing PDEs are transformed into a system of non-linear ODEs using appropriate non-similar transformations. The flexible Keller Box technique for second-order accurate implicit finite-difference is used. An excellent correlation is obtained when validating the present results against previous research results available in the literature, and the error analysis is also examined. The novelty of the present work lies in its unique incorporation of simultaneous multiple slip effects into the analysis of Buongiorno’s nanofluid flow over a stretching surface. It provides new insights into how combined slip conditions influence nanofluid transport characteristics. The study addresses the gap in existing literature by analysing the combined impact of slip conditions on Buongiorno’s nanofluid. It also fills the void in understanding how these slip effects jointly influence transport phenomena past a stretching surface. Implications of velocity, thermal, and concentration slips are illustrated graphically. Additionally, tabular values of the skin friction, Nusselt number, and Sherwood number are also given. Computations show that the velocity, temperature, and concentration profiles rise with an increase in the velocity slip. However, when the thermal slip is elevated, velocity, temperature, and concentration profiles decline, and the thinner thermal boundary layers reduce thermal and concentration gradients near the surface, diminishing fluid velocity. With greater concentration slip values, the velocity profile is enhanced; however, temperature and nanoparticle concentration both decay. The findings indicate that slip parameters play a crucial role in modulating flow behaviour under practical slip conditions. Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 117-140